The correlation between herd behavior and fear of missing out in the Vietnamese security market - Chi, Vu Mai; Anh, Nguyen Tuan; My, Nguyen Ha (International Journal of Innovative Research and Scientific Studies, 2025)
This research investigated the correlation between herd behavior and the fear of missing out (FoMO) in Vietnam’s security market, focusing on their combined impact on investor decisions and market stability. The authors used a survey of 212 individual investors whose data were collected through a questionnaire, with responses measured on a 7-point Likert scale from March 2024 to April 2024. Additionally, the article applied Spearman’s rank correlation coefficient to assess the relationship between these two behaviors. The findings demonstrated a significant positive correlation between herd behavior and FoMO. Investors who had a tendency for FoMO were more likely to follow herd behavior, especially during volatile markets; these behaviors tend to occur together. In conclusion, the article not only emphasized the importance of controlling psychological biases to enhance market stability but also addressed these behaviors that can help minimize speculative bubbles. The results of this research have important implications for improving Vietnam’s stock market efficiency and competitiveness. By recognizing potential biases that may influence their investment decisions, investors can adopt different strategies to mitigate the impact of such biases on their financial outcomes.